The applied sport science and medicine of powerlifting and para powerlifting: a systematic scoping review with recommendations for future research - Silverthorne, K.; Morrison, M.; Cowley, N.; Munteanu, G.; Creaby, M. W.; Timmins, R. G.; Chiang, C.-Y.; Weakley, J. (Sports Medicine, 2025)
Background: Powerlifting is a strength sport featuring some of the world`s strongest athletes. Recent decades have seen an exponential increase in research into the applied sport science and medicine of powerlifting and its Paralympic counterpart, para powerlifting. A scoping review of the area would provide athletes, coaches, policymakers, and researchers with an overview of the existing evidence to support performance, reduce injury, and foster further growth of these sports. Objectives: The primary objectives were to identify the current research into the applied sport science and medicine of powerlifting and para powerlifting, analyse the characteristics of the research, provide a brief summary of the research in each area of sport science and medicine, identify gaps in the current literature, and provide recommendations for future research. Methods: Systematic searches of SPORTDiscus, CINAHL, MEDLINE, and Scopus were performed from the earliest record to June 2025 (Open Science Framework registration: https://osf.io/fkjsz), and the reference lists of several pre-existing systematic reviews were manually searched. Studies were eligible for inclusion if they investigated powerlifting or para powerlifting as a sport or the applied sport science of powerlifters or para powerlifters from a performance or injury perspective. Results: A total of 2117 articles were identified in the database search, with three additional eligible studies discovered through other sources. In total, 218 studies met the inclusion criteria and were ultimately included in the review. The most researched sport science and medicine topic was physical qualities (n = 48), followed by competition (n = 45), training (n = 38), biomechanics (n = 36), nutrition and supplementation (n = 25), injury (n = 18), and psychology (n = 8). More than half of the included studies were published in 2020 or later, and researchers from the USA were the most prolific with 57 publications. Para powerlifting was investigated in 45 studies, which mostly originated from Brazil (n = 31). Participants represented varying levels of competition, powerlifting divisions, and age categories, although many studies did not clearly report these characteristics. Only seven studies investigated female athletes exclusively. Conclusion: This scoping review summarises the current literature investigating powerlifting and para powerlifting and can be used to enhance the applied sport science and medicine within the sports. While the amount of research has grown considerably in recent years, it is evident that certain demographics and areas remain under-investigated (e.g., injury mechanisms) or warrant updated examination (e.g., the prevalence of performance-enhancing drug use, which was last reported in 2003 and is currently unknown). Thus, this review highlights several areas for future research based on the gaps in the existing literature and provides a range of recommendations that can be implemented to improve reporting, transparency, and interpretation.